Psychometric properties of an arabic translation of the short boredom proneness scale (SBPS) in adults - Tia Khadra; Rabih Hallit; Diana Malaeb; Souheil Hallit; Feten Fekih-Romdhane; Sahar Obeid (BMC Psychology)
Abstract Background The Short Boredom Proneness Scale (SBPS) is a common tool for assessing individuals’ inclination toward Boredom. The Arabic version of the SBPS has not been validated despite the language being spoken by over 420 million people worldwide. Therefore, this study aims to translate the SBPS into Arabic and prove its psychometric properties on a sample of Arabic-speaking adults from Lebanon. Methods In this cross-sectional study, 410 participants (72.4% females, aged 18–52 years) were recruited to participate by completing the translated Arabic version of the SBPS through an online Google Forms survey. The validation of the scale was carried out using the Confirmatory Factor Analysis approach. Results Confirmatory Factor Analysis revealed a better fit after adding a correlation between residuals of items 2 and 6. The SBPS showed high internal reliability (ω = 0.81; α = 0.81). No significant differences were found in SBPS scores between males and females. Concurrent validity indicated that higher levels of anxiety, loneliness, and smartphone addiction were significantly associated with greater boredom proneness. Conclusion Our results confirm the reliability and validity of the Arabic version of the SBPS, suggesting its suitability for use among Lebanese general population adults. Further research is needed to assess its applicability in clinical settings and diverse Arabic-speaking populations. This concise and user-friendly tool potentially promotes cross-cultural research on boredom proneness.